2019
DOI: 10.1111/tmi.13344
|View full text |Cite
|
Sign up to set email alerts
|

Trends and socio‐economic disparities in catastrophic health expenditure and health impoverishment in China: 2010 to 2016

Abstract: objectives To investigate trends and socio-economic disparities in the catastrophic health expenditure (CHE) and health impoverishment in China after major reform of the health system and to examine the impacts of the chronic disease on CHE and impoverishment.methods We obtained data from four rounds of the China Family Panel Studies 2010-2016, with a sample size of 14 960 households. We defined CHE as the point at which annual household health payments exceeded 40% of annual capacity to pay. Impoverishment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 42 publications
5
46
5
Order By: Relevance
“…Here, we found that the CHE incidence of households with NCD patients in urban and rural areas were 19.88% and 26.02%, respectively, which are much higher than the results of another study on the overall proportion of households incurring CHE in China (urban households: 13.06%; rural households: 17.70%) [17]. It indicates that the risk tolerance of households with NCD patients to OOP medical expenditure is lower than the average level of Chinese households.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Here, we found that the CHE incidence of households with NCD patients in urban and rural areas were 19.88% and 26.02%, respectively, which are much higher than the results of another study on the overall proportion of households incurring CHE in China (urban households: 13.06%; rural households: 17.70%) [17]. It indicates that the risk tolerance of households with NCD patients to OOP medical expenditure is lower than the average level of Chinese households.…”
Section: Discussioncontrasting
confidence: 83%
“…Gwatidzo (2017) found that adults aged 50 or above in India were less likely to incur CHE due to diabetes mellitus medication use compared to China [16]. Zhao (2019) identified that the CHE incidence among rural households with NCD patients notably exceeded the average level of urban households with NCD patients in China [17]. Xie (2017) verified the main reasons why households with members suffering from NCDs in rural China were prone to CHE [18].…”
Section: Several Researches Have Investigated the Financial Catastrophementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies focus on the rural/urban, geographical/regional disparities [13][14][15][16], and sex disparities in cancer incidence and mortality [17,18], as well as disparities in treatment options [19]. In China, a few studies have examined the healthcare disparities among people with chronic diseases, such as hypertension, cardiovascular diseases, chronic obstructive pulmonary disease, and multimorbidity [20][21][22][23][24][25]. However, there is limited evidence of socioeconomic disparities in treatment, health service utilization, and financial protection among cancer patients following China's health system reform in 2009 [26].…”
Section: Introductionmentioning
confidence: 99%
“…8 From 1995 to 2012, the average annual growth rate of per capita transfer payments in the western region was 20.3%, higher than that in the central region. 9 Meanwhile, according to our calculations, the reimbursement rate in the central region (55.9%) was lower than that in the western region (58.2%). Therefore, it is obvious that the economic burden of diseases depends not only on the level of economic development of the region itself, but also on the healthcare needs and service utilization of the people and the design of the medical insurance system and other welfare systems.…”
Section: Poverty and Medical Impoverishment Under Different Medical Imentioning
confidence: 56%